Assessment of heavy metals and microbial contamination of gari from Liberia - Awoyale, W.; Asiedu, R.; Kawalawu, W.K.; Maziya-Dixon, Busie; Abass, A.; Edet, M.; Adetunji, M. (Wiley, 2018)
Cassava is a staple mostly eaten in the form of gari, after rice in Liberia. The local method of gari processing often leads to product contamination, thus, a study was done to assess the heavy metals and microbial contamination of gari in eight counties of the country. A total of sixty-one gari samples were collected and packaged in an airtight polyethylene bag for analyses, using standard methods. Results depict that the mean of the heavy metals in the gari samples is iron (Fe) 43.87 ppm, copper (Cu) 0.94 ppm, zinc (Zn) 5.49 ppm and aluminum (Al) 257.45 ppm. Yellow gari had the highest Fe (64.90 ppm), Cu (1.25 ppm) and Zn (7.85 ppm) content, but with the least Al content (87.15 ppm). The Fe content was lower in groundnut-fortified gari (42.93 ppm), and the Cu (0.70 ppm) and Zn (3.50 ppm) content were lower in groundnut-moringa-fortified gari. The samples and counties have no significant statistical effect (p > .05) on the heavy metals composition of the products. No microbial growth was observed in groundnut-fortified and groundnut-moringa-fortified gari but with coconut-fortified gari having the highest total fungi count of 800 CFU/g. The major fungi identified in the gari samples are Penicillium and Aspergillus spps., but with their counts within the regulated level. Therefore, the gari consumed in Liberia are safe except for the high Fe and Al content, which needs to be addressed with the use of unpainted stainless steel materials as food contact surfaces.